Measuring the potential for self-connectivity in global air transport markets: Implications for airports and airlines - Suau-Sanchez, Pere; Voltes-Dorta, Augusto; Rodríguez-Déniz, Héctor (Elsevier, 2016)
One of the strategies that air travellers employ to save money is self-connectivity, i.e. travelling with a combination of tickets where the airline/s involved do not handle the transfer themselves. Both airports and airlines, particularly low-cost carriers, have recently started catering to the needs of this type of passengers with the introduction of transfer fees or the development of self-connection platforms. The evidence provided by the existing literature, however, suggests that the degree of implementation of these strategies falls short of its true potential. In order to investigate how much self-connectivity could be observed in global air transport markets, this paper develops a forecasting model based on a zero-inflated Poisson regression on MIDT data. We identify the airports that have the highest potential to facilitate self-connections, as well as the factors that hinder or facilitate the necessary airline agreements at major locations. The results from this paper have many implications in regards to the widespread implementation of self-connection services and the future of the air travel industry
Keywords: Self-connectivity; Air transport networks; Connection builder; Poisson regression